Spiritual Education of Human Sexuality and Christian Responsibility for Children and Parents: Pendidikan Kerohanian Seksualitas Manusia dan Tanggung Jawab Kristen bagi Anak dan Orang Tua - Murni Hermawaty Sitanggang; Dodi Wijaya; Yulia Kurniawati (KHD Production, 2024)
Puberty often confuses teenagers who don't understand it. Therefore, it is essential to provide sex education to help children understand the phase they are experiencing. Not only children but parents also need to understand the developments that occur in their children so they can accompany their children in these turbulent times. This spiritual education aims to equip children and their parents with correct knowledge about human sexuality and its biblical responsibilities. The education was delivered in presentations, followed by an interactive discussion, and then closed with a conclusion. The result is that the counseling went well and was understood by the participants. The author suggests that this kind of activity be carried out regularly, considering the broad discussion of topics surrounding sex education. Keywords: education; sexuality; teens; parents